2022
DOI: 10.3390/ma15051703
|View full text |Cite
|
Sign up to set email alerts
|

Shear Performance of RC Beams Reinforced with Fe-Based Shape Memory Alloy Stirrups

Abstract: In this study, the shear performance of a reinforced concrete (RC) beam with Fe-based shape memory alloy (Fe-SMA) stirrups was evaluated experimentally and analytically. Five specimens that had a possibility of shear failure under four-point loading were prepared. The major experimental variables were the spacings (300 and 200 mm) between the Fe-SMA stirrups and whether the stirrups were activated or non-activated. The shear strength of the specimen reinforced with the Fe-SMA stirrups at a spacing of 200 mm wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Then, structural analysis is performed. The required steel reinforcement is then calculated to enhance the mechanical performance of structural elements such as ductility, tensile strength, and creep resistance [ 2 , 3 , 4 , 5 , 6 , 7 ]. Finally, the ultimate limit state and serviceability limit state requirements provided by design codes are checked [ 8 , 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Then, structural analysis is performed. The required steel reinforcement is then calculated to enhance the mechanical performance of structural elements such as ductility, tensile strength, and creep resistance [ 2 , 3 , 4 , 5 , 6 , 7 ]. Finally, the ultimate limit state and serviceability limit state requirements provided by design codes are checked [ 8 , 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…The use of SMA as shear reinforcement has been initially studied at small scale 'proof of concept', that used Ni-Ti wire spiral as internal shear reinforcement in various configurations utilizing pseudoelasticity at ambient temperatures in order to achieve ductile shear failures [17]. Another study used activated internal Fe-SMA stirrups in comparison to passive counterparts, reporting 8% increase in shear strength of the reinforced concrete beams with reduced shear cracking, also verified with numerical analysis [31]. Ni-Ti-Nb wires in a small scale study [18], wrapped around the cross section of rectangular beams as external activated reinforcement, exhibited 90 to 115% increase in shear strength of the retrofitted beams with more ductile shear failures.…”
Section: Shape Memory Alloys For Active Shear Strengtheningmentioning
confidence: 96%
“…In recent years, SMA has been used for shear reinforcement of RC beams in the form of internal stirrups. Ji et al [ 89 ] and Hong et al [ 90 ] studied the influence of Fe-SMA stirrup spacing and its effect shear performance and used finite element software for simulation and analysis. The results showed that SMA stirrups improved the shear strength and initial stiffness of the component and delayed the formation of cracks, verifying the effectiveness of the model.…”
Section: The Application Of Sma In Structural Components Of Buildingmentioning
confidence: 99%